Pengembangan Bahan Ajar Berbasis Komik Pada Materi Hidrokarbon - Pasaribu, Yenni Pintauli; Siregar, Lamtiar Ferawaty; Dakunya, Tresia Yumilda Somi (PendIPA Journal of Science Education, 2024)
This research aims to determine the validity of comic-based teaching materials on hydrocarbon materials. This type of research is R&D research using the ADDIE model. The subjects of this research were students of class XI Science at SMA Negeri 1 Tanah Miring. The instrument used in data collection was a questionnaire. The results of the research showed that the development of a comic-based module on hydrocarbon compound material was declared valid and practical in terms of validity. The material validation results were 100% in the very valid category, the media validation was 92% in the very valid category, and the student questionnaire was 86% in the very valid category. valid.  Based on the research results, the comic-based teaching module as teaching material for hydrocarbon compounds was declared valid  for use as teaching material for hydrocarbon compounds.